UV-Vis Activated Cu2O/SnO2/WO3 Heterostructure for Photocatalytic Removal of Pesticides - Enesca, Alexandru; Andronic, Luminita (Nanomaterials, 2022)
A three-steps sol–gel method was used to obtain a Cu2O/SnO2/WO3 heterostructure pow der, deposited as film by spray pyrolysis. The porous morphology of the final heterostructure was constructed starting with fiber-like WO3 acting as substrate for SnO2 development. The SnO2/WO3 sample provide nucleation and grew sites for Cu2O formation. Diffraction evaluation indicated that all samples contained crystalline structures with crystallite size varying from 42.4 Å (Cu2O) to 81.8 Å (WO3). Elemental analysis confirmed that the samples were homogeneous in composition and had an oxygen excess due to the annealing treatments. Photocatalytic properties were tested in the presence of three pesticides—pirimicarb, S-metolachlor (S-MCh), and metalaxyl (MET)—chosen based on their resilience and toxicity. The photocatalytic activity of the Cu2O/SnO2/WO3 heterostructure was compared with WO3, SnO2, Cu2O, Cu2O/SnO2, Cu2O/WO3, and SnO2/WO3 samples. The results indicated that the three-component heterostructure had the highest photocatalytic efficiency toward all pesticides. The highest photocatalytic efficiency was obtained toward S-MCh (86%) using a Cu2O/SnO2/WO3 sample and the lowest correspond to MET (8.2%) removal using a Cu2O monocomponent sample. TOC analysis indicated that not all the removal efficiency could be attributed to mineralization, and by-product formation is possible. Cu2O/SnO2/WO3 is able to induce 81.3% min eralization of S-MCh, while Cu2O exhibited 5.7% mineralization of S-MCh. The three-run cyclic tests showed that Cu2O/SnO2/WO3 , WO3 , and SnO2/WO3 exhibited good photocatalytic stability without requiring additional procedures. The photocatalytic mechanism corresponds to a Z-scheme charge transfer based on a three-component structure, where Cu2O exhibits reduction potential responsible for O2 production and WO3 has oxidation potential responsible for HO· generation
Keywords: pesticides; wastewater; photocatalysis; metal oxides; semiconductors